2015
DOI: 10.3390/v7042057
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Herpes Simplex Virus (HSV) Infection by Seminal Plasma and Semen Amyloids Implicates a New Target for the Prevention of HSV Infection

Abstract: Human herpesviruses cause different infectious diseases, resulting in world-wide health problems. Sexual transmission is a major route for the spread of both herpes simplex virus-1 (HSV-1) and -2. Semen plays an important role in carrying the viral particle that invades the vaginal or rectal mucosa and, thereby, initiates viral replication. Previously, we demonstrated that the amyloid fibrils semenogelin (SEM) and semen-derived enhancer of viral infection (SEVI), and seminal plasma (SP) augment cytomegalovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
0
21
1
1
Order By: Relevance
“…In agreement with previous observations performed with SP, 15 we found that SVF does not modify the course of HSV-2 primary infection in mice. On the other hand, contrasting with our observations indicating that mouse SVF does not affect in vitro HSV-2 infectivity, Torres et al 43 have reported that human SP enhances in vitro HSV-2 infectivity, suggesting that secretions from the epididymis and other male accessory sex glands might be responsible for this enhancing effect.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with previous observations performed with SP, 15 we found that SVF does not modify the course of HSV-2 primary infection in mice. On the other hand, contrasting with our observations indicating that mouse SVF does not affect in vitro HSV-2 infectivity, Torres et al 43 have reported that human SP enhances in vitro HSV-2 infectivity, suggesting that secretions from the epididymis and other male accessory sex glands might be responsible for this enhancing effect.…”
Section: Discussioncontrasting
confidence: 99%
“…An enhancement of infection by SEVI has also been reported for herpes simplex virus 1 (HSV-1), HSV-2, and HCMV (20,21), suggesting a similar mechanism of infection enhancement of these viruses. However, the role of amyloid fibrils in semen and the role of semen itself in HCMV infection have not been sufficiently explored.…”
mentioning
confidence: 73%
“…To further examine the anti-HCMV activity of SP, we investigated the role of seminal amyloids in infection (18). It has recently been reported that SEVI enhances HCMV as well as HSV-1 and -2 infections in vitro (20,21). First, we verified the infectionenhancing capacity of SEVI on HCMV in infection experiments.…”
Section: Inhibition Of Hcmv Infection By Seminal Plasma Is Independenmentioning
confidence: 94%
“…These results promote seminal amyloids as possible targets for intervention to prevent EBOV sexual transmission and seeding new infection chains that reignite an outbreak. enhancement roles for these fibrils for infection by simian immunodeficiency virus, cytomegalovirus, and herpes simplex virus (40)(41)(42).…”
mentioning
confidence: 99%